Doses de lodo de esgoto na fertilidade do solo após a colheita do girassol - Lobo, Thomaz Figueiredo; Lambert, Ricardo Alexandre; Grassi Filho, Helio [UNESP] (My University, 2012)
The agricultural use of sewage sludge as organic fertilizer is currently considered the most promising alternative for disposal of such waste due to its sustainability and its effect can be enhanced by combing the agricultural use and recovery of degraded areas. The objective of this study was to evaluate the effect of sewage sludge on soil fertility at different depths in the soil profile after the first year of application of this waste. The experiment was conducted at the Experimental Farm in San Manuel Faculty of Agronomic Sciences, UNESP, Botucatu Campus. We adopted the experimental design of randomized blocks consisting of six treatments and five repetitions. The treatments were: T0 - without N; T1 - 50 kg N ha-1 mineral fertilization; T2 - 25 kg N ha-1 of sewage sludge and 25 kg ha-1 of mineral fertilization; T3 - 50 kg N ha-1 sewage sludge; T4 - 75 kg N ha-1 sewage sludge; T5 - 100 kg N ha-1 sewage sludge. The evaluation of soil fertility was performed 4 months after the applications of sewage sludge. There was no change in pH, OM, CEC and V%, Mg, Mn and SB, at all depths of the soil according to the application of sewage sludge. The application of sewage sludge increased the concentration of H+Al, S, Cu, Fe and Zn in soil surface layer (0 to 0,10 m deep), however did not affect the soil fertility in the top subsurface (0, 20 to 0,40 m deep).
Doses of sewage sludge on soil fertility after sunflower harvesting
Keywords: Biosolid; Fertilization and nutrient recycling